The Effect Integrity and Objectivity Auditor Intern to Effectivity Audit Intern with democratic Leadership Style as Variable Moderated on the Inspectorate districts X - Dewa Putu Bayu Permadi; A.A.G.P Widanaputra (E-Jurnal Akuntansi, 2025)
The purpose of this study was to determine the effect of integrity and objectivity on the effectiveness of internal audit with democratic leadership style as a moderating variable at the X Regency Inspectorate. This research was conducted at the Office of the Inspectorate of X Regency. The number of samples taken as many as 32 auditors, with saturated sampling method. Data was collected through a survey method with data collection techniques using a questionnaire. The analysis technique used is Moderated Regression Analysis.